Dualisme Konsep Pungutan Liar sebagai Tindak Pidana Korupsi dan Tindak Pidana Umum - Tolib Effendi; Rusmilawati Windari (Integritas : Jurnal Antikorupsi, 2022)
The absence of delineation regarding the imposition of illegal levies under Presidential Regulation No. 87 of 2016 on the Illegal Levy Eradication Task Force has driven law enforcers, especially the Illegal Levy Eradication Task Force (Saber Pungli), to be varied in establishing delineation in the enforcement of illegal levy affairs. The imposition of illegal levies is treated by law enforcers as a corruption offence as well as an extortion offence. The issues raised in this research concern how the offence of imposing illegal levies should be formulated in alignment with criminal law concepts and the reality in society, as well as whether the imposition of illegal levies should be categorised as a corruption offence. The aim of this paper is to review the regulation of the imposition of illegal levies as a corruption offence, as well as the implementation of the law. This research uses a normative research method with statute and conceptual approaches. The legal sources were analysed deductively from the general to the specific. The concept used in this review is the basic concept in criminal law regarding general criminal laws and special criminal laws. Based on the results, this research concluded that the government should confirm the delineation of acts categorised as the imposition of illegal levies, regardless of whether it is part of the corruption offence category or not.